Exogenous glomalin boosts kumquat seedling growth by enhancing soil structure and biochemical activity - Hao, Yong; Lu, Wei; Liu, Chun-Yan; He, Jiadong (Frontiers in Plant Science, 2025)
IntroductionGlomalin-related soil protein (GRSP), a nitrogen-linked glycoprotein secreted by arbuscular mycorrhizal fungi, is recognized for its role in enhancing soil physical and chemical properties and improving ecosystem stability. However, the dose-dependent effects of exogenous easily extractable GRSP (EE-GRSP) on perennial fruit crops such as citrus remain largely unexplored.MethodsThe effects of varying strengths (1/4, 1/2, 3/4, and full strength (0.027 mg·mL–1)) of exogenous EE-GRSP on kumquat (Fortunella japonica) seedling growth, root architecture, and rhizosphere soil properties (enzyme activities, aggregate stability, organic carbon content, and GRSP content) were investigated.ResultsEE-GRSP significantly promoted kumquat growth and root development, with the 3/4 strength (0.020 mg·mL–1) exhibiting pronounced positive effects on plant biomass and optimized root architecture. Concurrently, this optimal dosage markedly enhanced soil aggregate stability (mean weight diameter +92.9%) and stimulated key rhizosphere enzyme activities (up to 64%), correlating with increased soil organic carbon and de novo GRSP content. These improvements followed a parabolic dose-response, with excessive full-strength EE-GRSP diminishing benefits compared to the 3/4 dose.DiscussionThese findings unequivocally establish that exogenous EE-GRSP can effectively promote citrus growth primarily by fostering robust synergistic soil-plant feedbacks through concomitant improvements in both soil physical structure (e.g., aggregate stability) and biochemical processes (e.g., enzyme activity and carbon sequestration). This study advances our mechanistic understanding of glomalin-mediated soil-plant interactions and highlights EE-GRSP as a promising and valuable soil amendment for sustainable citrus cultivation, urging further validation under diverse field conditions.